Influence pH to Rate Anthocyanins Extract Senggani Fruit ( Melastoma malabathricum Auct, non Linn) - Ratih Indrawati; Gervacia Jenny.R; Maulidiyah Salim; Bagus Muhammad Ihsan; Ari Widiyantoro (Jurnal Penelitian Pendidikan IPA, 2024)
One of the plants that can be used as a natural dye is senggani fruit. This study aimed to determine the effect of acid pH on the anthocyanin levels of the senggani fruit extract. The method used in this study uses UV-Vis Spectrophotometry. The sample was senggani fruit extract, added with an acidic pH solution (1-6) with 3 repetitions for 18 samples. Based on the results of research that has been carried out, the average anthocyanin levels at pH 1 are 2.00% with a bright red color; pH 2 is 1.63% with a red-orange color, pH 3 is 1.45% with an orange color, pH 4 is 2.05 % with brownish red color, pH 5 is 1.38% with brownish orange color, and pH 6 is 1.11% with light brown color. Based on statistical tests using Simple Linear Regression, Ha was accepted so that it could be concluded that there was an effect of acid pH on the anthocyanin levels of the senggani fruit. Based on a study that has been done, it is known that the sourer the pH solution is, the taller the anthocyanin obtained. Matter happens Because absorbance is comparable with the rate of anthocyanin something sample.